Pembelajaran Mandiri Mahasiswa Progam Studi Pendidikan Agama Islam Melalui Reservasi Method - Septemiarti, Isnaini (LP. Ma'arif Janggan Magetan, 2024)
In today's era of technological development, independent learning is a necessity that must be possessed by students. Independent learning encourages students to be active by having the ability and skills to think critically about changes in existing situations well. It is hoped that students are able to make a positive contribution to changes and/or solving learning problems in society. Student learning independence helps students achieve goals, skills, and expertise in learning. This study aims to develop student independent learning through the reservation method in the form of creating scientific journal articles. This study uses a qualitative approach with descriptive analysis. The subjects in this study were fifth semester students of the Islamic religious education study program at STAI Nurul Hidayah Selatpanjang. The main instrument of this study was the researcher himself with support in the form of questionnaires and interviews made according to the established indicators. The results of the study showed that students had good independent learning abilities, this can be seen from the aspects of learning independence that they have including motivation, self-confidence, discipline, responsibility and initiative. The success of independent learning can also be seen from the changes in attitudes and abilities of students to follow the learning process, in addition it was also found that independent learning of students through the reservation method in the form of making scientific articles makes students have characters with the ability to elaborate between intellectual abilities and theoretical concepts with life in society. Independent learning is able to raise intellectual and spiritual awareness in a balanced way that is integrated into each course.